Stranieri controllo, accoglienza e integrazione negli Stati italiani (XVI-XIX secolo) - Marco Meriggi (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2020)
"Administering the foreigner" is the title of a large research program of whom this volume is part.The chapters use a wide range of sources, and offer a sort of survey of the available documentation; for example: ancient regime censuses, matrimonial acts, traveler memoirs, registers of guest-houses and other reception centers, passports and other registration and travel documents, such as laissez passer, safe conducts, security and verification cards.In this long-lasting perspective, the theme of mobility highlights the relationships, tensions and negotiations between individuals, communities and state and local powers, around the issues of identifying people and ensuring the coexistence between different cultures and religions.